INFORMATION AND COMMUNICATION TECHNOLOGIES (ICT) AS AN ENABLER FOR MULTIGENERATIONAL LIVING - Andri Farber; Theresa Hodapp; Thomas Keller; Enrico Neff (European Scientific Journal, ESJ, 2014)
How can the implementation of information and communication technologies (ICT) support multigenerational living? In the recent years it could have been observed that the rapidly ageing society is a strong incentive to find new ways to mitigate the risks given by the demographic transformations. An active approach to face these challenges is the concept of multigenerational living, where the exchange of neighborly help within the community based on solidarity is an integral part for the insurance of a supportive system. The need for ICTbased solutions within a multigenerational community cannot be reduced to the quantitative demographic processes. The on-going social changes, success factors of multigenerational living and intergenerational relationships had to be considered. As a result the relevant application areas for ICT were identified as the enhancement of the independence of elderly people, support of organization structures within the community, and the inclusion of external support. Within these areas there is a wide range of existing ICT solutions that can support multigenerational living. For future ICT solutions multigenerational communities can take advantage of the fact that the given social environment may lead to facilitated implementation, especially in regard to the inclusion of elderly people in the information society. This literature review tries to summarize to current results of this subject